The academic institutionalization of sociological science in Belarus - Danilov, Alexander N. (Journal of the Belarusian State University. Sociology, 2020)
The opening of the Institute of Sociology of the National Academy of Sciences of Belarus in 1990 became a notable fact in the history of Belarusian science and completed the process of academic institutionalization of sociological science in Belarus. This process was connected with the activity of G. P. Davidyuk and E. M. Babosov which are the leaders of the reappearing Belarusian sociology. Sociology in Belarus has passed its difficult path of acknowledgement. This process was stretched out in time, contradictory, complex and multifaceted. The final phase of institutionalization of sociological science was occurred on the eve of great achievements and the collapse of the USSR. The authorities did not adequately assess the situation in society and it was apparent. It was not a coincidence that the leaders of the ruling party made a statement that «we do not know the society in which we live». The sociology as a social science with necessary research tools for understanding contemporary society became most demand in such times. The Institute of Sociology has turned into a large and topranked research center for 30 years of his work and become one of the main sources of obtaining the social knowledge about contemporary society and the processes taking place in it, about a person and his social wellbeing. The new institute has launched research on the methodological and theoretical problems of contemporary sociology, in the field of sociology of personality, science and culture, labor and demography, youth, the social structure of Belarusian society, the attitudes of various groups to social institutions, the dynamics of the political system of Belarus, the characteristics of the public opinions, etc.